Phosphorogenic Iridium(III) bis‐Tetrazine Complexes for Bioorthogonal Peptide Stapling, Bioimaging, Photocytotoxic Applications, and the Construction of Nanosized Hydrogels - Yip, Alex Man‐Hei; Lai, Calvin Kin‐Ho; Yiu, Ken Shek‐Man; Lo, Kenneth Kam‐Wing (Angewandte Chemie International Edition, 2022)
The dual functionality of 1,2,4,5‐tetrazine as a bioorthogonal reactive unit and a luminescence quencher has shaped tetrazine‐based probes as attractive candidates for luminogenic labeling of biomolecules in living systems. In this work, three cyclometalated iridium(III) complexes featuring two tetrazine units were synthesized and characterized. Upon photoexcitation, the complexes were non‐emissive but displayed up to 3900‐fold emission enhancement upon the inverse electron‐demand Diels–Alder (IEDDA) [4+2] cycloaddition with (1R,8S,9s)‐bicyclo[6.1.0]non‐4‐yne (BCN) substrates. The rapid reaction kinetics (k2 up to 1.47×104 M−1 s−1) of the complexes toward BCN substrates allowed effective peptide labeling. The complexes were also applied as live cell bioimaging reagents and photocytotoxic agents. One of the complexes was utilized in the preparation of luminescent nanosized hydrogels that exhibited interesting cargo delivery properties. Novel iridium(III) bis‐tetrazine complexes that displayed significant phosphorogenic response toward (1R,8S,9s)‐bicyclo[6.1.0]non‐4‐yne (BCN) derivatives were synthesized and characterized. The complexes were exploited for peptide stapling and cross‐labeling of BCN‐modified peptides. They were also utilized in bioimaging, singlet oxygen photosensitization, and the construction of luminescent nanosized hydrogels.